Avaliação dos impactos do Programa Crediamigo em população de baixa renda de Fortaleza - Silva, Rita Josina Feitosa da (2010)
This study is about the microcredit program of the BNB, Crediamigo, based on the following issues: (i) There was a change in living conditions of clients who enrolled in the program? (II) And if there was, to what extent these changes are directly related Crediamigo. Its central objective is to assess the impacts of Crediamigo living conditions of low-income beneficiaries, verifying their relation with the processes of social inclusion and citizenship. The methodology, data were collected on the general Crediamigo and, based on these data, the unit was focused Montese Crediamigo, for being the first unit to implement the program and serve a customer base in poor condition. In this research, we selected the low-income clients of the unit that relied on three-year program. The research methodology resulted from a combination of quantitative procedures (semi-structured questionnaires) and qualitative (open-ended interviews, with stories of life). We note that although the data point to an immediate impact on the income of low-income beneficiaries and their families, the result obtained does not allow us to say that the credit would result in improvements in living conditions in general, leading to social inclusion and citizenship, because, when it comes to living conditions that were historically constructed in a structurally exclusionary context, one realizes the limits of the reach of Crediamigo and the need to maintain alliances with broader social programs.